A computational multi-scale approach for brittle materials - Ernesti, Felix (Schriftenreihe Kontinuumsmechanik im Maschinenbau, 2023)
Materials of industrial interest often show a complex microstructure which directly influences their macroscopic material behavior. For simulations on the component scale, multi-scale methods may exploit this microstructural information. This work is devoted to a multi-scale approach for brittle materials. Based on a homogenization result for free discontinuity problems, we present FFT-based methods to compute the effective crack energy of heterogeneous materials with complex microstructures.